Performance Services of Home Care-Based Health and Marine Ambulance Telemedicine in Makassar City(Case Study of Health Service Performance Based on Home Care and Marine Ambulance Telemedicine on Barrang Lompo Island, Makassar City) - Hargitayanti Hargitayanti; Muh.Akmal Ibrahim; Hasniati Hasniati (Institute of Computer Science (IOCS), 2021)
The purpose of this study was to measure the performance of home care-based health services and marine ambulance telemedicine in Makassar City. because public health has an important role in efforts to improve the quality of human resources, poverty alleviation and economic development. The Human Development Index puts health as one of the main components of measurement besides education and income. With the weakening of health services based on Home Care and Ambulance Telemedicine Marine, the community feels that they do not get effective services, where people expect to get better and more effective health services, but in fact they find that health services are getting weaker. This study uses a quantitative descriptive method, with data collection techniques using a questionnaire. with 307 respondents based on the Slovin formula. The results of this study indicate that the performance of home care-based health services and marine ambulance telemedicine in Makassar City is still categorized as not good, this is seen from 29.5% indicating that the performance of health services is still not good.